A Study of Scientific Attitude among Learners in Botswana - Singh, Vijay P. (SCHOOL SCIENCE, 2014)
This paper describes the analysis of the scientific attitude of varied sample, including learners from Junior Secondary and Senior Secondary school levels and also a group of prospective science teachers from a college of secondary education in Botswana. The tool used for the study was a Likert type five-point Scientific Attitude Scale (SAS) developed and standardised by the investigator. The tool contained items on six of essential component behaviours of the scientific attitude like open mindedness; belief in truth/facts; appreciation of nature of Science; free from superstitions; curiosity to learn/explore new facts and phenomena; and objectivity. The analysis of the scores indicated that the level of scientific attitude of some of the learners was very low, whereas a good proportion of sample showed an average level. No significant difference was noticed in the attitude of male and female respondents. A need of serious, sound and sustainable planning of the school Science curriculum and its dissemination was reflected by the study. As way forward, the investigator has proposed strategies for enhancing the opportunities for the effective development of scientific attitude by creating an enabling environment of Science learning in the educational institutions in Botswana